Evaluation of the Effects of Aqueous Extract of Sarcocephalus latifolius on Sexual Behaviour in Male Rats - (:unkn) unknown (My University, 2023)
Background: Sarcocephalus latifolius, a plant of the Rubiaceae family, is found exclusively in tropical Africa, more particularly in sub-Saharan West Africa, stretching from Senegal to Zaire, but is also found as far east as Sudan (Sudan-Guinean zone). The leaves of this plant are used in traditional African medicine to treat numerous pathologies such as infertility. Aims/Objective: The present study aims to evaluate the effects of the aqueous extract of Sarcocephalus latifolius leaves on sexual parameters in male rats. Methods: The sexual parameters (latency of the mating position, latency of intromission, latency of ejaculation and mean copulation interval) were assessed by the classical method by administering distilled water, sildenafil citrate (reference molecule) called Viagra at the dose of 5 mg/kg of body weight and the aqueous extract of Sarcocephalus latifolius leaves at the dose of 1000 mg/kg of body weight per day for eight days to three batches of male rats respectively. These parameters were determined over a period of thirty minutes. Results: The results obtained show that the aqueous extract of Sarcocephalus latifolius leaves at a dose of 1000 mg/kg of body weight significantly (P < .001) decreases the latency time of mating position and the latency time of intromission, whereas this extract significantly (P < .001) increases the latency time of ejaculation and the average copulation interval. Conclusion: Aqueous extract of Sarcocephalus latifolius leaves has aphrodisiac properties which are due to sterols, flavonoids and saponosides.
Keywords: African Research